Mechanism of activation of an N-ras oncogene of SW-1271 human lung carcinoma cells. - Yuasa, Y (1984)
An N-ras-related transforming gene was detected in the human lung carcinoma cell line SW-1271 and molecularly cloned. The lesion responsible for its acquisition of transforming activity was localized to a single nucleotide transition from A to G in codon 61 of the predicted protein. This lesion in the second exon results in the substitution of arginine for glutamine at this position. These findings, together with previous studies, indicate that the activation of ras oncogenes in human tumors is most commonly due to point mutations at one of two major "hot spots" in the ras coding sequence.